USE OF BIG DATA IN EDUCATION MANAGEMENT: BUILDING DATA-POWERED DECISION MAKING - Muh Ibnu Sholeh (Promis, 2023)
This study aims to analyze the impact of using big data in education management in an effort to improve the quality of education as a whole both in terms of the implementation, benefits and challenges of using big data in education management. The method used in this research is library research method. Data were obtained from various sources such as scientific journals, books, seminar papers and other relevant publications related to research topics both offline and online. The data obtained were analyzed using an interactive qualitative model. This data analysis technique consists of data collection, data reduction, data presentation and drawing conclusions. The results of this research are first, the implementation of big data in education management through data collection. Big data storage and processing. Data analysis for decision making and use of data analysis tools. Second, the benefits of using big data in education management include increasing the efficiency of education administration. Provide in-depth insight and information about students. Support curriculum development that focuses on student needs. Provides objective measurement of teacher and school performance. And improve predictions and interventions against educational risks. And third, challenges in implementing big data include challenges in collecting and analyzing complex data. Privacy protection and data security. Infrastructure system development. And an increase in user capabilities and skills. This research contribution can provide a deeper understanding of how the use of big data in education management can have a positive impact on improving the overall quality of education and can also provide a more detailed comparison between data-driven decision-making methods and traditional methods in the educational context.